Pengembangan Medıa Pembelajaran Interaktıf Power Poınt Berbasıs Problem Based Learnıng Pada Materı Suhu Dan Kalor - Puspita Prima Tri Handayani (LPPM UNIVERSITAS PGRI SILAMPARI, 2023)
This research aims to develop problem-based learning-based interactive learning media on temperature and heat materials for eleventh grade students. The research method carried out is a type of research and development with a 4D model (define, design, development, disseminate). Data were obtained obtained from the validation assessment of physics educators of SMA N 1 Minggir and SMA N 1 Godean. feasibility of problem-based learning-based interactive learning media on temperature and heat material using ideal standard deviation (SBi) with an average result of 3.75 with a very decent category. The developed media attracts students' attention and can increase students' knowledge and motivate students to learn physics. In addition, problem-based learning-based powerpoint interactive learning media on temperature materials can instill a deep understanding of concepts.